2019
DOI: 10.3390/ani9020054
|View full text |Cite
|
Sign up to set email alerts
|

KISS1 Suppresses Apoptosis and Stimulates the Synthesis of E2 in Porcine Ovarian Granulosa Cells

Abstract: Previous studies have strongly recommended that KISS-1 metastasis suppressor (KISS1) plays an essential gatekeeper of the initiation of reproductive maturation in mammals. However, KISS1 has been recently reported to highly express in ovarian granulosa cells (GCs). But the biological functionalities of KISS1 on cell apoptosis, cell cycle, and synthesis of estradiol-17β (E2) have not been explored in GCs. In this study, using porcine GCs as a cellular model, the overexpression plasmid of KISS1 was built to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Kisspeptin at 50 and 100 nM concentrations increased the E 2 production by 1.6-1.8 fold (Table 2) and is consistent with the report in the porcine GCs (Xin et al, 2019). Further, upregulation of STAR and CYP19A1 gene transcripts by 100 nM Kp (Table 3) supports the stimulatory effect of 100 nM Kp on E 2 production.…”
Section: Discussionsupporting
confidence: 87%
“…Kisspeptin at 50 and 100 nM concentrations increased the E 2 production by 1.6-1.8 fold (Table 2) and is consistent with the report in the porcine GCs (Xin et al, 2019). Further, upregulation of STAR and CYP19A1 gene transcripts by 100 nM Kp (Table 3) supports the stimulatory effect of 100 nM Kp on E 2 production.…”
Section: Discussionsupporting
confidence: 87%
“…Kisspeptin can regulate animal reproduction by regulating follicular development through the paracrine or autocrine pathway in the gonads. Kisspeptin treatment promotes progesterone secretion in cultured bovine granulosa cells [ 24 ], while transfection of the kiss1 gene into porcine ovarian granulosa cells promotes steroid secretion [ 25 ]. Our research group also showed that kisspeptin could promote the secretion of steroid hormones and cell proliferation in ovarian granulosa cells of Tan sheep in vitro (unpublished data), but the specific molecular mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has suggested that a high expression level of PIK3C is associated with follicular development and subfertility in mice [44]. A high mRNA level of PDK1 depresses cell apoptosis and affects cell entry in porcine GCs [45]. FOXO3 -specific-depletion in GCs decreases both cell proliferation and apoptosis of GCs and disrupts follicular growth in mice [46], and a lower mRNA expression of FOXO3 in GCs is involved in infertility in women [47].…”
Section: Discussionmentioning
confidence: 99%